An Alternative Approach to Decellularize Whole Porcine Heart - Methe, Ketaki (Biores Open Access, 2014)
Scaffold characteristics are decisive for repopulating the acellular tissue with cells. A method to produce such a scaffold from intact organ requires a customized decellularization protocol. Here, we have decellularized whole, intact porcine hearts by serial perfusion and agitation of hypotonic solution, an ionic detergent (4% sodium deoxycholate), and a nonionic detergent (1% Triton X-100). The resultant matrix was characterized for its degree of decellularization, morphological and functional integrity. The protocol used resulted in extensive decellularization of the cardiac tissue, but the cytoskeletal elements (contractile apparatus) of cardiomyocytes remained largely unaffected by the procedure although their membranous organelles were completely absent. Further, several residual angiogenic growth factors were found to be present in the decellularized tissue.